2006
DOI: 10.1117/12.653546
|View full text |Cite
|
Sign up to set email alerts
|

Automatic colonic polyp detection using multiobjective evolutionary techniques

Abstract: Colonic polyps appear like elliptical protrusions on the inner wall of the colon. Curvature based features for colonic polyp detection have proved to be successful in several computer-aided diagnostic CT colonography (CTC) systems. Some simple thresholds are set for those features for creating initial polyp candidates, sophisticated classification scheme are then applied on these polyp candidates to reduce false positives. There are two objective functions, the number of missed polyps and false positive rate, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2008
2008
2010
2010

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 11 publications
0
17
0
Order By: Relevance
“…For each vertex on the colon surface, geometric and curvature features are calculated and filtered. Candidate polyps are formed on the surface from connected clusters of filtered vertices (12). The filtering and clustering are optimized by a multiobjective evolutional technique (12, 13).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For each vertex on the colon surface, geometric and curvature features are calculated and filtered. Candidate polyps are formed on the surface from connected clusters of filtered vertices (12). The filtering and clustering are optimized by a multiobjective evolutional technique (12, 13).…”
Section: Introductionmentioning
confidence: 99%
“…Candidate polyps are formed on the surface from connected clusters of filtered vertices (12). The filtering and clustering are optimized by a multiobjective evolutional technique (12, 13). A knowledge-based polyp segmentation is performed on the 3D volume data, starting from the identified surface region (14).…”
Section: Introductionmentioning
confidence: 99%
“…The problem was formulated as a multi-objective integer program, and solved by means of a new evolutionary algorithm named Maximum Coverage at minimum Cost (MC 2 ) that we proposed and tested in this work. We have shown that MC 2 is able to find much better solutions than the powerful and widely used EMA SPEA2 [3]- [5]. The key is the way in which we exploit the knowledge about the concavity of common pricing functions of ISPs.…”
Section: Outputmentioning
confidence: 99%
“…• We show that our EMA is capable of finding much better solutions than another powerful and highly utilized EMA, namely, the Strength Pareto Evolutionary Algorithm version 2 (SPEA2) [3]- [5], while complying with the network capacity and budget constraints.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation